Discursive Conflict in "Benito Cereno". Noble Savage versus Wild Man - Jesús Benito Sánchez (Miscelánea: A Journal of English and American Studies)
This article departs from the classical controversy on whether Melville's auythoritative point of view in "Benito Cereno" can be discerned. Taking for granted the impossibility to ascertain Melville's position with regards to slavery, this article proposes to analyze Delano's rendering of the story. This analysis uncovers the discursive conflict generated by the existence of two contradictory images of the black man —as Noble Savage and as Wild Man— deployed by Delano.